Global Housing Cycles - Igan, Deniz (IMF Working Papers; Working Paper ;, 2012)
Housing cycles and their impact on the financial system and the macroeconomy have become the center of attention following the global financial crisis. This paper documents the characteristics of housing cycles in a large set of countries, and examines the determinants of house price movements. Empirical analysis shows that house price dynamics are mostly driven by income and demographics but fluctuations in these fundamentals and credit conditions can create deviations from the implied equilibrium path. We conclude with a discussion of the macroeconomic implications of house price corrections.